AgriTech4Tunisia Innovation Challenge: Call for applications now open! - Mounir, Aya; Loiseau, Camille (2025)
The CGIAR Accelerate for Impact Platform and partners are launching in December 2025 the AgriTech4Tunisia Innovation Challenge to support early-stage practical, scalable agri-tech solutions in one of the region’s most dynamic ecosystems.